Relationship Between the COVID-19 Pandemic and Ecological, Economic, and Social Conditions - Murányi, Attila; Varga, Bálint (Frontiers in Public Health, 2021)
COVID-19 pandemic had huge impacts on the global world, with both a negative impact on society and economy, but a positive one on nature. But this universal effect resulted in different infection rates from country to country. We analyzed the relationship between the pandemic and ecological, economic, and social characteristics. All of these data were collected in 140 countries at 6 timepoints. Correlations were studied using univariate and multivariate regression models. The world was interpreted as a single global ecosystem consisting of ecosystem units representing countries. We first studied 140 countries around the world together, and infection rates were related to per capita GDP, Ecological Footprint, median age, urban population, and Biological Capacity, globally. We then ranked 140 countries by infection rate and created 4 equal groups, each with 35 countries. In the first group, the infection rate was very high and was related to the Ecological Footprint (consumption) and GDP per capita (production). This group is dominated by developed countries and their ecological characteristics have proven to be particularly significant. In groups 2, 3, and 4, infection rates were high, moderate, and low, and were primarily associated with median age and urban population. In the scientific discussion, we have interpreted why infection is high in developed countries. Sustainable ecosystems are balanced, unlike the ecosystems of developed countries. According to science, the resilience and health of both natural ecosystems and humans are closely linked to the world of microbial communities. Our results suggest that both the economy and society need to be in harmony with nature, creating sustainable ecosystems in developed countries as well.